Pengaruh Penggunaan Elektroliser Tipe Wet Cell Dengan Variasi Larutan Elektrolit Terhadap Daya Dan Torsi Sepeda Motor JUPITER MX Tahun 2010 - Ertonson Timothy Loblobly; Husin Bugis; Ranto Ranto (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The objectives of this study were to investigate the effect of using Wet Cell type electrolyzer on the power and torque of Jupiter MX motorcycles in 2010. To investigate the effect of variations in electrolyte solutions on the use of Wet Cell type electrolyzers on the power and torque of Jupiter MX motorcycles in 2010.This research was conducted at the Automotive Laboratory for Mechanical Engineering Education, Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta and at PT. Motocourse Technology (MOTOTECH) Yogyakarta. This research is a descriptive quantitative research. The research design used was experimental design. The research sample used a Jupiter MX motorbike in 2010. This experimental tool used a Wet Cell type electrolyzer using a variety of pure water, KOH and NaOH electrolyte solutions. The data collection method used in this research is the experimental method.The results of this study are the use of the Wet Cell type electrolyzer has an effect on the power and torque of the Jupiter MX motorcycle in 2010, namely an increase in power of 0.97 HP and an increase in torque of 1.88 N.m compared to testing standard engine conditions. The use of 24 gram / liter KOH solution in the Wet Cell type electrolyzer has the highest increase in power and torque levels compared to other variations in the ratio of solutions. There was an increase in power of 0.39 HP and an increase in torque of 0.3 N.m compared to the power and torque of using a Wet Cell type electrolyzer with water as an electrolyte solution without a catalyst and 1.36 HP and 2.18 N.m compared to the power and torque of the standard state. The use of 24 gram / liter NaOH solution has the lowest rate of increase, there is an increase in power of 1.33 HP and 1.84N.m compared to the power and torque of the standard state.